Perbedaan Prestasi Belajar Ditinjau dari Tipe Kepribadian Siswa Kelas IV SDN se-Kecamatan Kebumen - Kurnianingsih, Hani Oktavia; Joharman, Joharman; Suhartono, Suhartono (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2021)
One of the internal factors that influence students learning achievement is personality. This research aimed to find a personality type that gives a better influence on the learning achievement of the fourth grade students of elementary schools in Kebumen sub-district in Academic Year 2017/2018. This research is a quantitative research with comparative method. The selected samples were taken by cluster random sampling technique with the help application of SPSS version 21. The number of samples in this research was 320 students in eleven elementary schools in Kebumen sub-district. The method of data were collected by questionnaire technique and by using document. Data were analyzed by using independent sample t test with significance level of 0.05 (5 %). In testing of independent sample t test the value of Sig. was obtained 0.000 < α (0.05), the average learning achievements of introvert students was 81.60, and the average learning achievements of extrovert students was 80,08 which means that rejected H0. Based on the analysis and discussion of research results, it can be concluded that there were significant differences between the learning achievements of introvert students and the learning achievements of students who have extrovert personality and introvert personality types showed a better influence on the learning achievements of the fourth grade students of elementary schools in Kebumen sub-district in Academic Year 2017/2018 that evidenced by the average learning achievements of introvert students is higher than extrovert students.